Effects of strength training on ankle injuries in soccer players: a systematic review - Daniel Alejandro Jerez Mayorga; Andres Felipe Villaquiran Hurtado (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Purpose: The purpose of this systematic review was (I) to determine the quality of evidence from studies evaluating the effects of strength training on the incidence of ankle injuries in soccer and (II) to determine the effectiveness of strength training on the incidence of ankle injuries in soccer. Methods: Preferred Reporting Items for Systematic Reviews (PRISMA) statements were considered using keywords associated with ankle injuries, strength training, and soccer. The following four databases were used: PubMed, Web of Science, Scopus, and SPORTDiscus. The quality of evidence for the articles included in this review was assessed using the PEDro scale. Results: Of the 721 articles retrieved, two were included in this study. The total population included in the review was 132 male participants, including professional soccer players and youth players. Strength training in young soccer players could reduce the risk of injury and improve parameters related to sports performance; however, the two articles included in this review found no statistically significant differences in injury incidence between the proprioceptive training and control groups.  Conclusions: The articles included in this review had a high risk of bias, indicating low quality of evidence. In addition, it was impossible to determine whether strength training effectively reduced ankle injuries in the soccer players.